Stereotaxic atlas of the infant rat brain at postnatal days 7–13 - Chen, Yu-Nong; Zheng, Xin; Chen, Hai-Lin; Gao, Jin-Xian; Li, Xin-Xuan; Xie, Jun-Fan; Xie, Yu-Ping; Spruyt, Karen; Shao, Yu-Feng; Hou, Yi-Ping (Frontiers in Neuroanatomy, 2022)
Recently, researchers have paid progressively more attention to the study of neural development in infant rats. However, due to the lack of complete intracerebral localization information, such as clear nuclear cluster boundaries, identified main brain structures, and reliable stereotaxic coordinates, it is difficult and restricted to apply technical neuroscience to infant rat’s brain. The present study was undertaken to refine the atlas of infant rats. As such, we established a stereotaxic atlas of the infant rat’s brain at postnatal days 7–13. Furthermore, dye calibration surgery was performed in P7–P13 infant rats by injecting Methylene blue, and sections were incubated in Nissl solutions. From the panoramic images of the brain sections, atlases were made. Our article has provided the appearance and measurements of P7–P13 Sprague–Dawley rat pups. Whereas the atlas contains a series of about 530 coronal brain section images from olfactory bulbs to the brainstem, a list of abbreviations of the main brain structures, and reliable stereotaxic coordinates, which were demonstrated by vertical and oblique injections with fluorescent dye DiI. The present findings demonstrated that our study of P7–P13 atlases has reasonable nucleus boundaries and accurate and good repeatability of stereotaxic coordinates, which can make up for the shortage of postnatal rat brain atlas currently in the field.